(untitled) (Medical Forum Monthly, 2022)
Objective: To find mean change in post-dialysis blood pressure after dry weight reduction among patients on hemodialysis. Study Design: Quasi-Experimental study Place and Duration of Study: This study was conducted at the Dialysis Unit, Nephrology Department, Sir Ganga Ram Hospital, Lahore from June 2017 to March 2018. Materials and Methods: Sixty patients were enrolled. The mean of the blood pressures was calculated as a baseline. Dry weight was reduced through ultrafiltration by additional weight loss of 0.9 kg/10 kg per dialysis. Follow-up was done after 4 weeks and a mean change in post-dialysis systolic and diastolic BP was recorded. Results: Forty six (76.7%) were males and 14 (23.3%) were females. The mean age was 45.4±11.8 years. Mean SBP at baseline was 160.7±12.4 mmHg and 152.0±12.8 mmHg at 4 weeks, which is statistically significant (p=0.000).Mean DBP at baseline was 93.2±3.1 mmHg and 89.5±7.9 mmHg at 4 weeks, which is also statistically significant (p=0.000). Conclusion: The reduction of dry weight is an effective maneuver to improve BP control in hemodialysis patients.